2008
DOI: 10.1515/znb-2008-0112
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and anti-HIV and Antitumor Activities of New Coumarin Derivatives

Abstract: A new series of coumarin and benzofuran derivatives were synthesized as potential non-nucleoside reverse transcriptase inhibitors (NNRTIs) by reacting, separately, 4-bromomethylcoumarins, their sulphonyl chlorides, and ethyl 3-(bromomethyl)-6-methoxy-1-benzofuran-2-carboxylate with different imidazoles and their benzo analogs. The antiviral (HIV-1, HIV-2) properties of the newly synthesized compounds were investigated in vitro and all compounds were found to be inactive, except 10 which showed inhibition of HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…2 was prepared similarly to the method reported in the literature [28]. The substitution of chlorine for an imidazolyl group was achieved by performing a reaction with 2-methyl-4-nitroimidazole, following the method described by Al-Soud et al [59]. A polymerisable groups was introduced into the coumarin structure by reacting the amine substituted coumarin 4 with 4-vinylbenzylchloride to give the secondary amine 5.…”
Section: Synthesis Of Polymerisable Fluorescent Dyesmentioning
confidence: 99%
“…2 was prepared similarly to the method reported in the literature [28]. The substitution of chlorine for an imidazolyl group was achieved by performing a reaction with 2-methyl-4-nitroimidazole, following the method described by Al-Soud et al [59]. A polymerisable groups was introduced into the coumarin structure by reacting the amine substituted coumarin 4 with 4-vinylbenzylchloride to give the secondary amine 5.…”
Section: Synthesis Of Polymerisable Fluorescent Dyesmentioning
confidence: 99%
“…3 Piperazinyl linked ciprofloxacin dimers reported as potent antibacterial agents against resistant strains. 4 Sulfonamide and substituted sulfonamide derivatives are important category of pharmacophores that have a wide spectrum of biological and pharmacological applications such as antimalarial, 5 antimicrobial, 6 antibacterial, 7,8 anticancer, 9 antifungal, 10 antihelmintic, 10 antioxidant, 11 antiHIV, 12 antitumor, 12 antiplasmodial, 13 antineoplastic, 14 antiproliferative 15 activities and additionally known to act as 5-HT 6 , 5-HT 7 receptor antagonists, 16,17 A2B and CXCR3 antagonists, 18,19 11b-HSD, 20 histone deacetylase (HDAC) inhibitors, 21 b-secretase (BACE1) inhibitors 22 and dual PI3K/mTOR inhibitors. 23 In recent years, literature reveals that the research interest and applications of antioxidants have constantly gathered high importance to eradicate the oxidative stress in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Yarim and her co-workers previously reported various piperazine derivatives with high cytotoxic activity against liver (HUH-7, FOCUS, MAHLAVU, HepG-2, Hep-3B), breast (MCF-7, BT20 and T47D), colon (HCT-116), gastric (KATO-3), cervix (HeLa) and endometrial (MFE-296) cancer cell lines [9][10][11] . According to anticancer activity studies of benzothiazolepiperazine backbone, arylsulphonamides and arylthiol derivatives have potent cytotoxicity against a large scale of cancer cell lines such as breast (MCF-7), hepatocellular (HepG-2), prostate (DU-145) cancers and CD4 + human acute T-lymphoblastic leukaemia (CCRF-CEM) 12,13 . In this study, with the aid of aforementioned studies, we reported the synthesis, purification and characterization of novel compounds which contain benzothiazole-piperazine backbone in their molecular structure.…”
Section: Introductionmentioning
confidence: 99%